Longitudinal assessment of neuropsychological and temporal/spatial gait characteristics of elderly fallers: taking it all in stride - MacAulay, Rebecca K.; Allaire, Ted D.; Brouillette, Robert M.; Foil, Heather C.; Bruce-Keller, Annadora J.; Han, Hongmei; Johnson, William D.; Keller, Jeffrey N. (Frontiers in Aging Neuroscience, 2015)
Gait abnormalities are linked to cognitive decline and an increased fall risk within older adults. The present study addressed gaps from cross-sectional studies in the literature by longitudinally examining the interplay between temporal and spatial aspects of gait, cognitive function, age, and lower-extremity strength in elderly “fallers” and “non-fallers”. Gait characteristics, neuropsychological and physical test performance were examined at two time points spaced a year apart in cognitively intact individuals aged 60 and older (N = 416). Mixed-model repeated-measure ANCOVAs examined temporal (step time) and spatial (stride length) gait characteristics during a simple and cognitive-load walking task in fallers as compared to non-fallers. Fallers consistently demonstrated significant alterations in spatial, but not temporal, aspects of gait as compared to non-fallers during both walking tasks. Step time became slower as stride length shortened amongst all participants during the dual task. Shorter strides and slower step times during the dual task were both predicted by worse executive attention/processing speed performance. In summary, divided attention significantly impacts spatial aspects of gait in “fallers”, suggesting stride length changes may precede declines in other neuropsychological and gait characteristics, thereby selectively increasing fall risk. Our results indicate that multimodal intervention approaches that integrate physical and cognitive remediation strategies may increase the effectiveness of fall risk interventions.